2022
DOI: 10.3390/ma15134478
|View full text |Cite
|
Sign up to set email alerts
|

From Quantum Materials to Microsystems

Abstract: The expression “quantum materials” identifies materials whose properties “cannot be described in terms of semiclassical particles and low-level quantum mechanics”, i.e., where lattice, charge, spin and orbital degrees of freedom are strongly intertwined. Despite their intriguing and exotic properties, overall, they appear far away from the world of microsystems, i.e., micro-nano integrated devices, including electronic, optical, mechanical and biological components. With reference to ferroics, i.e., functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Even so, in the recent years the interest raised by the observation of exotic electronic properties in quantum materials seeks new strategies in nanofabrication which go beyond conventional processes as a matter of tunability and compatibility for the exploitation of advanced features in next-generation electronics. [117,118] Phase nanoengineering, with the aim of crafting thoroughly the physical and structural properties of low-dimensional system, represents a key viable route in this regard. Particularly, it is promising for patterning periodic and arbitrarily-shaped grayscale (i.e., 3D) energy landscapes for controlling the electronic properties, for fabricating electronic devices based on 2D materials, [119] and for moving toward 3D nanostructuring.…”
Section: Electronicsmentioning
confidence: 99%
“…Even so, in the recent years the interest raised by the observation of exotic electronic properties in quantum materials seeks new strategies in nanofabrication which go beyond conventional processes as a matter of tunability and compatibility for the exploitation of advanced features in next-generation electronics. [117,118] Phase nanoengineering, with the aim of crafting thoroughly the physical and structural properties of low-dimensional system, represents a key viable route in this regard. Particularly, it is promising for patterning periodic and arbitrarily-shaped grayscale (i.e., 3D) energy landscapes for controlling the electronic properties, for fabricating electronic devices based on 2D materials, [119] and for moving toward 3D nanostructuring.…”
Section: Electronicsmentioning
confidence: 99%
“…Rashba semiconductors (FERSC) have been recently disclosed as a new class of multifunctional materials to enrich electronic and spintronic device technologies. [1][2][3][4][5][6][7][8][9] The unique feature of FERSC is the fundamental breaking of the inversion symmetry caused by a ferroelectric (FE) lattice distortion, which leads to a large spin splitting of the electronic band structure in k-space by the Rashba effect [10,11] (Figure 1a). The direction of the spin polarization, that is, the helicity of the spin texture is locked to the FE polarization.…”
Section: Ferroelectricmentioning
confidence: 99%
“…[12,13] This remarkable property is singular to this class of multifunctional materials and is sought-after for spintronic applications such as spin field effect transistors, non-volatile and bipolar mem ories as well as programmable transistors for nematics and logic operations. [8,[13][14][15][16] The development of FERSC demands materials exhibiting ferroelectricity, semiconductor properties and a sizeable Rashba effect at the same time. Recent theoretical studies have suggested a number of potential FERSC candidates like complex oxides, [17][18][19] perovskites [20][21][22] or 2D materials, [15,23,24] but so far, FERSC have been demonstrated experimentally only for the IV-VI class of semiconductors (see Figure 1b).…”
Section: Ferroelectricmentioning
confidence: 99%
“…Ferroelectric Rashba semiconductors (FERSC) have been recently disclosed as a new class multifunctional material to enrich electronic and spintronic device technologies [1][2][3][4][5][6][7][8][9] . The unique feature of FERSC is the fundamental breaking of the inversion symmetry caused by a ferroelectric (FE) lattice distortion, which leads to a large spin splitting of the electronic band structure in k-space by the Rashba effect [10,11] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This means that in a FERSC the spin polarization can be externally controlled and reversed by an applied electric field via a non-volatile and switchable poling process [12,13] . This remarkable property is singular to this class of multifunctional materials and is sought-after for spintronic applications such as spin field effect transistors, non-volatile and bipolar memories as well as programmable transistors for nematics and logic operations [9,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%